Global attractors of impulsive infinite-dimensional systems - Kapustyan, O. V.; Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We study the existence of global attractors in discontinuous infinite-dimensional dynamical systems, which may have trajectories with infinitely many impulsive perturbations. We also select a class of impulsive systems for which the existence of a global attractor is proved for weakly nonlinear parabolic equations.